2017
DOI: 10.1111/jpm.12406
|View full text |Cite
|
Sign up to set email alerts
|

How people from Chinese backgrounds make sense of and respond to the experiences of mental distress: Thematic analysis

Abstract: Introduction Late presentation and low utilization of mental health services are common among Chinese populations. An understanding of their journey towards mental health care helps to identify timely and appropriate intervention. Aim We aimed to examine how Chinese populations make sense of the experiences of mental distress, and how this understanding influences their pathways to mental health care. Method We undertook in-depth interviews with fourteen people with mental health problems (MHPs) and sixteen fa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 47 publications
0
9
0
Order By: Relevance
“…Formal help-seeking becomes synonymous with the acquisition of (additional) stigmatising and oppressive labels and diagnoses [ 48 , 81 , 88 , 89 , 102 , 103 ], particularly where faith and other communities and families encourage a view that (mental) illness is equated with weakness and moral failings [ 48 , 65 , 78 , 88 , 102 – 105 ]. A diagnosis of mental illness can therefore be seen as equivalent to a form of social death, which “ cuts short any types of aspirations and hope ” [ 103 ], particularly in the context of precarious minority identities, racist social exclusion, and strong interdependence in ethnic minority communities in response to that [ 49 , 69 , 75 , 78 , 81 , 88 , 89 , 91 , 102 , 103 , 106 , 107 ]. As such, for some families, the need for social survival in the context of social marginalisation results in emotional suppression and the censoring of conversations around mental illness [ 64 , 76 , 78 , 83 , 91 , 98 100 , 105 ].…”
Section: Resultsmentioning
confidence: 99%
“…Formal help-seeking becomes synonymous with the acquisition of (additional) stigmatising and oppressive labels and diagnoses [ 48 , 81 , 88 , 89 , 102 , 103 ], particularly where faith and other communities and families encourage a view that (mental) illness is equated with weakness and moral failings [ 48 , 65 , 78 , 88 , 102 – 105 ]. A diagnosis of mental illness can therefore be seen as equivalent to a form of social death, which “ cuts short any types of aspirations and hope ” [ 103 ], particularly in the context of precarious minority identities, racist social exclusion, and strong interdependence in ethnic minority communities in response to that [ 49 , 69 , 75 , 78 , 81 , 88 , 89 , 91 , 102 , 103 , 106 , 107 ]. As such, for some families, the need for social survival in the context of social marginalisation results in emotional suppression and the censoring of conversations around mental illness [ 64 , 76 , 78 , 83 , 91 , 98 100 , 105 ].…”
Section: Resultsmentioning
confidence: 99%
“…Two studies focused on meaning making about MHP in migrant communities and highlighted the relevance of culturally held meanings about mental health not only in individuals’ understanding, but also their behaviour. In studies with Egyptian families in Australia (Endrawes, O'Brien, & Wilkes, 2007) and Chinese families in England (Yeung, Irvine, Ng, & Tsang, 2017), cultural stigma was found to hamper relatives’ understanding because of the belief that MHP should not be discussed outside the family. In combination with religious traditions and language barriers, family obligations were found to perpetuate silence (Endrawes et al, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…Endrawes et al (2007) found that older, first‐generation immigrants tended to be more sceptical of medication and hospital treatment. Yeung et al (2017) reported that male relatives in Chinese families took longer than women to label their partner's unusual behaviours as “mental health” rather than “personality.” In both studies, relatives drew upon both medical and religious conceptualizations to support their sense making.…”
Section: Resultsmentioning
confidence: 99%
“…A review also described that migrants tend to prefer seeking help from their social network, rather than to seek help from mental health services [ 18 ]. Another study in the UK described that the use of mental health services of Chinese migrants with mental illness was delayed because their social networks lacked the knowledge of mental health services [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%